Adaptive Spelling in Immersive Reality: The Impact of Gamified VR and LLMs on Young Learners’ English Color Word Acquisition - Jalal Safari Bazargani; Abolghasem Sadeghi-Niaraki; Xinyu Shi; Soo-Mi Choi (IEEE Access)
Spelling is a crucial language skill, yet traditional instruction often relies on rote memorization rather than meaningful learning. Despite various approaches to spelling instruction, the potential of virtual reality (VR) along with the integration of gamification and LLMs, remains underexplored. This study explores a VR-based, gamified approach using LLM-driven adaptive learning to improve spelling acquisition of English color words among young learners. The study employed a quasi-experimental, pre-test-post-test design with a control group. The participants were 50 male students aged 10, divided into an experimental group (N=25) that used the LLM-enhanced VR game and a control group (N=25) that received traditional instruction. The VR intervention consisted of a three-stage game built on the whole-word approach, featuring gamified elements and adaptive feedback from an LLM. Data were collected via spelling tests (pre-test, immediate post-test, and delayed post-test), user experience surveys, and semi-structured interviews. Results showed that the VR-based approach, significantly improved spelling performance and engagement. Specifically, the experimental group demonstrated substantially higher scores in both immediate vocabulary uptake and long-term retention after one week compared to the control group. Furthermore, qualitative and survey data indicated the VR experience was perceived as significantly more interesting, effective, and motivating. These findings highlight the potential of immersive, gamified learning environments to enhance spelling education, offering an effective alternative to conventional methods.